2005
DOI: 10.1111/j.1085-9489.2005.10107.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological and magnetic resonance analysis of sciatic nerves in the tellurium model of neuropathy

Abstract: Ingestion of tellurium (Te), a toxic element, produces paralysis of the hind limbs in weanling rats that is due to temporary, segmental demyelination of the sciatic nerves bilaterally. Weanling rats were fed a 1.1% elemental Te diet and sacrificed at various time points for histological and magnetic resonance (MR) analysis of the sciatic nerves. No controls exhibited impairments of the hind limbs, whereas Te-treated animals became progressively impaired with increased Te exposure. Toluidine blue-stained nerve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Measures associated with the IE water pool can also offer further insight into pathology. One group found that both inflammation and tellurium‐induced demyelination in rat sciatic nerve caused the IE peak to shift to higher T 2 s . Barnes et al demonstrated, using a two‐point method for T 2 calculation, that the presence of edema in cat brain can lead to a lengthening in T 2 , likely due to an increase in IE T 2 .…”
Section: Previous Reproducibility Results For Mwf and Gmt2 Metricsmentioning
confidence: 99%
“…Measures associated with the IE water pool can also offer further insight into pathology. One group found that both inflammation and tellurium‐induced demyelination in rat sciatic nerve caused the IE peak to shift to higher T 2 s . Barnes et al demonstrated, using a two‐point method for T 2 calculation, that the presence of edema in cat brain can lead to a lengthening in T 2 , likely due to an increase in IE T 2 .…”
Section: Previous Reproducibility Results For Mwf and Gmt2 Metricsmentioning
confidence: 99%
“…In addition to the above mentioned human validation studies, a number of animal studies have also demonstrated a strong correlation between myelin water and various myelin histological stains in both peripheral nervous system and CNS animal models .…”
Section: Validation Of Myelin Water Imagingmentioning
confidence: 96%
“…Moreover, T 1 , T 2 , and MT provide quantitative assessment of tissue pathology. In particular, they offer additional information about the processes of demyelination and axonal loss (1)(2)(3)(4), inflammation (5), infarction (6), white matter edema (7), tumor malignancy (8), and ischemia (9). Both tissue relaxation and MT parameter estimates are important in designing MRI pulse sequences that aim to accentuate contrast between normal and pathologic tissue.…”
mentioning
confidence: 99%